EFFICIENT USE OF WATER RESOURCES IN IRRIGATION OF AGRICULTURAL CROPS - U. A. Juraev; K. B Rustamova; O. M. Yusupova (Bright Mind Publishing, 2025)
The article presents the results of studies devoted to water-saving irrigation technology on steep slopes and clarifies the elements of irrigation technology for contour irrigation in the conditions of southern Uzbekistan.
Keywords: Water conservation, furrow irrigation,water distribution, microburrows, contour irrigation, steep slope, polymer K-9, irrigation technique, irrigation technology, the greatest slope.